Analysis of Solar Energy Efficiency and its Applications in Sustainable Electricity Production" (Comprehensive Journal of Science, 2026)
Solar energy is witnessing a major expansion as it is considered one of the most important renewable energy sources that contribute to reducing carbon emissions and providing sustainable electricity solutions. This study aims to analyze the efficiency of solar energy systems and the factors affecting their performance, while presenting a comparison between different types of solar cells (see Table 1) and analytical figures illustrating the study results (see Figure 1). The paper summarizes a set of recommendations that contribute to raising the efficiency of electricity generation based on solar energy. It also relies on a scientific review of the latest technologies used to increase efficiency, such as high-performance cells and Maximum Power Point Tracking (MPPT) algorithms.
Keywords: Solar Energy, Efficiency, Photovoltaic (PV) cells, Sustainable Electricity, Renewable Energy